Effect of Manganese Oxide Doping of Tin Oxide Thin Films on the Optical and Structural Properties - Mahmood, Sara S.; Hasan, Bushra A.; Rauuf, Aws F. (Iraqi Journal of Science, 2024)
Tin oxide pure and manganese oxide doped (SnO2:Mn2O3) films were grown on a glass substrate in vacuum by pulsed laser deposition (PLD) technique (using Nd: YAG Laser) at different ratios of Mn2O3 (0, 3, 5, 7, 9) % wt. The structural and optical properties were studied. The X-ray diffraction (XRD) studies showed the structure nature of the films to be polycrystalline and rutile tetragonal. The optical transmittance spectra and optical constants of the prepared thin films, such as extinction coefficient (k), refractive index (n), and real (εr) and imaginary parts (εi) of the dielectric constant, were investigated. The values of the energy band gap increased from 3.5 eV to 3.55 eV with increasing the doping concentration.